2009
DOI: 10.1080/03610920802192505
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Parameters of the Generalized Exponential Distribution in Presence of Hybrid Censoring

Abstract: The two most popular censoring schemes are type-I and type-II censoring schemes. Hybrid censoring scheme is a mixture of type-I and type-II censoring schemes. In this paper we mainly consider the analysis of hybrid censored data when the lifetime distribution of the individual item is a two-parameter generalized exponential distribution. It is observed that the maximum likelihood estimators can not be obtained in closed form. We propose to use the EM algorithm to compute the maximum likelihood estimators. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…We can some numerical method to solve (7) and (8) Escobar [17] reported that the confidence interval in based on the asymptotic theory of ) ln(λ is superior to that of λˆ. α .…”
Section: Confidence Intervalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can some numerical method to solve (7) and (8) Escobar [17] reported that the confidence interval in based on the asymptotic theory of ) ln(λ is superior to that of λˆ. α .…”
Section: Confidence Intervalsmentioning
confidence: 99%
“…Balakrishnan and Iliopoulos [3] formally proved that these conjectures are indeed true thus validating the exact inferential procedures developed by all these authors. Since then, more references about hybrid censoring can refer to Ebrahimi [4] ,Chandrasekhar, et al [5] ,Balakrishnan and Xie [6] ,Kundu et al [7] Balakrishnan et al [8] Cheng Conghua, Chen Jinyuan [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus,ĉ = c (h+1) andk = k (h+1) for which h is the smallest integer such that the convergence criterion holds. The maximization procedure can be done as given by Kundu and Pradhan [23]. First, c (h+1) is obtained by solving the …xed point type equation…”
Section: Parameter Estimationmentioning
confidence: 99%
“…Extensive work has been done by several authors on GE( ) distribution. Some of the recent references on GE( ) distribution are (Gupta & Kundu, 2001), (Gupta & Kundu, 2002), (Jaheen, 2004), (Raqab & Madi, 2005), (Kundu, et al, 2005), (Gupta & Kundu, 2007), (Kundu & Gupta, 2008), (Kundu & Pardhan, 2008) and (Kim & Song, 2010). …”
Section: Introductionmentioning
confidence: 99%